Can Bacillus paranthracis cause bacteremia in a T-ALL patient? WGS-based diagnosis - Süzük Yıldız, Serap; Polat, Ayşegül; Yalçın, Süleyman; Ölmez, Mert Emre; Darçın, Tahir; Özdel, Kerem; Mumcuoğlu, İpek; Dal, Tuba (The Journal of Infection in Developing Countries, 2025)
Introduction: Most of Bacillus spp. generally avirulent species in healthy patients, but if there is a fragile in the patient, especially their immune system, Bacillus spp. can be an agent for infections. Case Report: In this case, we report that Bacillus paranthracis, diagnosed by whole genome sequencing, is responsible for bacteremia in a T-ALL patient. A 26-year-old male patient was diagnosed with T-cell acute lymphoblastic leukemia. Bacillus paranthracis was isolated from two sets of blood cultures obtained from a patient with febrile neutropenia. Results: The bacteria was identified as Bacillus cereus group in a routine microbiology laboratory by MALDI TOF MS. Then whole genome sequencing (WGS) confirmed its name as Bacillus paranthracis. The pathogenicity of the bacterium, especially in immunocompromised patients, has also been demonstrated by WGS. Conclusions: In a microbiology laboratory, the use of Whole Genome Sequencing (WGS) is important for diagnosing diseases, especially in immunocompromised patients. It will serve the management of these patients for infection control.